Exploring the Role of Strategic Intervention in Form-focused Instruction - Trendak, Olga (Second Language Learning and Teaching,, 2015)
The monograph is devoted to the notion of strategic intervention and its application in the foreign language classroom, in particular with reference to teaching grammar structures. The first four chapters, which are theoretical in nature, address such concepts as form-focused instruction, language learning strategies and strategies-based instruction. The last chapter provides insight into the results of a study investigating the grammar learning strategies employed by advanced learners of English. Additionally, the chapter presents the views of foreign language teachers on the idea of introducing strategy training in the foreign language classroom. The book closes with the discussion concerning the implementation of strategy training and its value in teaching  target language grammar.